ANALISIS GAYA BAHASA DALAM LIRIK LAGU ENU DENG LIPA SONKE KARYA IVAN NESTORMAN - Nadia; Marselus Robot; Margareta P.E Djokaho (STKIP Subang, 2026)
This study aims to describe the types of stylistic devices found in the lyrics of the song “Enu Deng Lipa Songke” by Ivan Nestorman. The song’s lyrics were selected as the subject of this study because they contain linguistic elements rich in aesthetic meaning and the cultural values of the Manggarai people. This study employs a qualitative descriptive method with a stylistic approach based on Gorys Keraf’s theory. The data source for this study is the lyrics of the song “Enu Deng Lipa Songke” by Ivan Nestorman, while the research data consists of words, phrases, clauses, and sentences containing stylistic devices. Data collection was conducted through listening, reading, and note-taking, while data analysis was carried out through the stages of data reduction, data classification, data analysis and interpretation, and drawing conclusions. The results of the study show that the lyrics of the song “Enu Deng Lipa Songke” contain two groups of rhetorical devices: figures of comparison and figures of emphasis. The figures of comparison consist of four instances of metaphor and four instances of symbolism. Emphatic figures of speech consist of one instance of repetition, one instance of parallelism, and one instance of climax. Meanwhile, figures of contrast and irony were not found in the song’s lyrics. The use of metaphors and symbolism serves to reinforce the expression of admiration, love, and hope, as well as to represent the cultural identity of the Manggarai people. Meanwhile, repetition, parallelism, and climax are used to emphasize feelings, reinforce the message, and create beauty and structural coherence in the lyrics. Thus, the lyrics of “Enu Deng Lipa Songke” not only possess aesthetic value but also serve as a medium for preserving local culture through the use of language rich in meaning and symbolism.